2017
DOI: 10.1002/anie.201705562
|View full text |Cite
|
Sign up to set email alerts
|

Stereospecificity in Intramolecular Photoredox Reactions of Naphthoquinones: Enantioselective Total Synthesis of (−)‐Spiroxin C

Abstract: Intramolecular photoredox reactions of naphthoquinone derivatives were found to proceed in a stereospecific manner. This method was used as a basis for the enantioselective total synthesis of (-)-spiroxin C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…The second step is the spiro‐acetalization by an external oxidant to construct oxabicycle 6 . The utility of this approach has been demonstrated by the first enantioselective total synthesis of (−)‐spiroxin C ( 3 ) …”
Section: Figurementioning
confidence: 99%
“…The second step is the spiro‐acetalization by an external oxidant to construct oxabicycle 6 . The utility of this approach has been demonstrated by the first enantioselective total synthesis of (−)‐spiroxin C ( 3 ) …”
Section: Figurementioning
confidence: 99%
“…We reported the stereospecific CÀHf unctionalization by the photoredox reactiono fn aphthoquinones, and its utility was demonstrated by the sucssessful total synthesis of (À)-spiroxin C, am arine antibiotic (Scheme 28). [46] The key questionw as whether or not the stereogenicity in the chiral, non-racemic naphthoquinone 109 is reflected in the photoredox product 110.T he answer was affirmative, as as tereospecific reaction proceeded to give spiroether 110 as as ingle isomer.T he benzylic CÀHb ond in 109 was replaced by aC ÀOb ond in 110 with retention of the configuration.…”
Section: Stereospecific Càhf Unctionalizationmentioning
confidence: 99%
“…We reported the stereospecific C−H functionalization by the photoredox reaction of naphthoquinones, and its utility was demonstrated by the sucssessful total synthesis of (−)‐spiroxin C, a marine antibiotic (Scheme ) . The key question was whether or not the stereogenicity in the chiral, non‐racemic naphthoquinone 109 is reflected in the photoredox product 110 .…”
Section: Utility In Organic Synthesismentioning
confidence: 99%
“…6,7 Among these compounds, Palmarumycin BG5 showed excellent cytotoxicities against human breast carcinoma MCF-7 with IC 50 7.6 mM and promyelocytic leukemia HL60 with IC 50 1.9 mM, Guignardins E, F and Palmarumycin C 1 exhibited signicant cytotoxicities against 10 human tumor cell lines, such as MCF-7 with LD 50 8.79, 6.48 and 3.08 mM, HL60 with LD 50 2.94, 3.06 and 2.90 mM, and HeLa with LD 50 1.32, 0.38 and 1.24 mM et al 6 Many reports related to the total synthesis, structure modication, and biological activity evaluation of the spirobisnaphthalene natural products have appeared in recent years. [8][9][10][11][12][13][14][15][16][17][18][19][20] The synthesis of Palmarumycin CP 17 and its analogues were completed in our laboratory, and the bioassay results showed that they have antifungal activity against several phytopathogens. 21 Because of the interesting larvicidal activity of Palmarumycin B 6 against Aedes albopictus, its limited access in the fermentation extract of the endophytic fungus Berkleasmium sp., and the importance of the halogen atom in the A-ring.…”
Section: Introductionmentioning
confidence: 99%